How is the New Public Management applied in the occupational health care system? - decision-makers' and OH personnel's views in Finland - Rissanen Sari; Hakulinen Hanna; Lammintakanen Johanna (BMC, 2011)
Abstract Background In many countries occupational health care system is in change. Occupational health studies are mainly focused on occupational health substance and content. This study offers new perspectives on municipal OHS and its operations from management perspective. Aim The aim of this study is to analyse how New Public Management (NPM) doctrines are applied in the Finnish occupational health care system (OHS). The main focus is to describe and compare the views of decision-makers' and OH workers within the framework of NPM. Methods The data were collected by semi-structured interviews from 17 municipal decision-makers' and 26 municipal OH workers. Data was analyzed by examining coded data in a theory-driven way according to Hood's doctrine of NPM. Results The doctrines were not as compatible with the OH personnel view as with the decision-makers' view. Decision-makers and OH personnel highlighted the strict criteria required for operation evaluation. Moreover, decision-makers strongly accentuated professional management in the public sector and the reorganization of public sector units. These were not equally relevant in OH personnel views. In OH personnel views, other doctrines (more attention to performance and accomplishments, emphasizing and augmentation of the competition and better control of public expense and means test) were not similarly in evidence, only weak evidence was observed when their importance viewed as medium by decision-makers. Neither of the respondents group kept the doctrine of management models of the private sector relevant. Conclusions The NPM and Hoods doctrine fitted well with OH research. The doctrine brought out view differences and similarities between decision-makers and OH personnel. For example, policymakers highlighted more strongly the structural change by emphasizing professional management compared to OH personnel. The need for reorganization of municipal OH, regardless of different operational preconditions, was obvious for both decision-makers and OH personnel. The adaptation of more clarify management to a municipal context is not trouble-free. The municipality systemic structure, complex operational environment, and reconciliation of political and officer authority set challenges to management of municipalities.